Research on Response Postures of Subway Train in Straight Line Collision - Shuhao Liu; Yiqun Yu; Yi Li; Rongqiang Liu; Rong Zhang (Applied Sciences)
A six-car subway train finite element model was developed to investigate possible response postures under impact accidents. Considering the plastic deformation of carriages and weak points of the train front, the simulation included two conditions: train–train collision and collision with an obstacle. Comprehensive response postures were obtained. A one-dimensional dynamic theory model was established to verify the rationality of the FEM model. The influence of impact speed, impact angle, and impact position on the energy consumption and response postures were discussed. The results show that one accident condition is accompanied by a variety of response postures. The main factors of climbing are asynchronism of yaw and pitch motions of adjacent carriages and plastic deformation of carriage ends, which leads to vertical arch. In oblique and front-side collision, the lateral force and the deviation of train front cause rapid derailment, and large lateral movement of the front and lateral buckling happen subsequently.